Thyroid fine-needle aspiration biopsy positively correlates with increased diagnosis of thyroid cancer in South Korean patients. Issue 1 (December 2017) - Cho, Yoon; Kim, Do; Park, Eun-Cheol; Han, Kyu-Tae
Abstract Background The incidence of thyroid cancer among South Koreans is more than 10-fold greater than its incidence in other countries, although its associated mortality rate is similar. Amidst concerns regarding the over-diagnosis of thyroid cancer related to gradually expanded medical testing in South Korea, we hypothesized that the number of thyroid fine-needle aspiration biopsies has led to increased diagnosis of thyroid cancer. Methods We used data from the National Health Insurance Service National Sample Cohort 2003–2013, which included all medical claims filed for the 1, 122, 456 people in a nationally representative sample. We performed a Poisson regression analysis using generalized estimating equation to investigate the relationship between the number of thyroid fine-needle aspiration biopsies and the newly diagnosed cases of thyroid cancer. Results The study included 60 annual patients per 100, 000 individuals out of 11, 024, 548 person-years. The number of biopsies per 100, 000 patients positively correlated with increased incidence of thyroid cancer diagnosis (per 100 biopsy cases: RR = 1.108; 95% CI: 1.090–1.126;P  < 0.0001). Such relationships were greater in males, patients with a higher socioeconomic status, and patients from regions with relatively less accessibility to biopsies. Conclusion Our findings suggest that a higher number of thyroid fine-needle aspiration biopsies per 100, 000 individuals in a specific Si-Gun-Gu is positively associated with excessively increased diagnosis of thyroid cancer. Regarding the continually increasing thyroid cancer incidence in South Korea, healthcare professionals and policy makers should consider proper guidelines for recognizing the role of thyroid fine-needle aspiration biopsies in the potential over-diagnosis of thyroid cancer.